Dlouhodobé výsledky léčby zlomenin diafýzy femuru u dětí léčených Bryantovou vertikální trakcí - Urban, Jiří; Toufar, P; Kloub, Martin (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF THE STUDY The paper aimed to evaluate the long-term outcomes of the treatment of diaphyseal femur fractures in children treated with Bryant's vertical traction. Moreover, we also assessed the size of overgrowth in the injured femur. MATERIAL AND METHODS The study included 23 patients with 23 femoral shaft fractures treated with Bryant's vertical traction at our department in 2009-2014. The following parameters were assessed: sex, ïnjured side, weight, age, mechanism of injury, potential abuse, type of fracture, duration of traction, and total length of hospital stay. The healing time of the fracture was the same as the duration of traction. Also assessed was the size of femoral shortening after the removal of traction, the presence of skin complications in the course of treatment and potential development of compartment syndrome. At the mean follow-up of 47.8 months (range 22-85 months) from the date of injury the patients were evaluated clinically and radiologically for: length of limbs, presence of rotational deformity, range of motion of knee and hip joints, potential pain or limping, potential scoliosis of the spine and presence of scars after traction. Finally, through a questionnaire we learned about the opinions of parents as to the treatment method and about the possibility of home traction. RESULTS All the fractures healed. There was a total of 17 injured boys and 6 injured girls. Whereas 12 patients sustained a fracture of the left femur, 11 patients sustained a fracture of the right femur. The mean weight of patients at the time of injury was 13.9 kg (range 5-20 kg). The mean age at the time of traction was 30.8 months (range 1-70 months). The injury most frequently occurred from various falls, altogether in 15 cases (65.2%). Traffic accidents were registered as the cause of injury in 3 cases (13%). No abuse was confirmed. The average duration of traction was 19.8 days (range 8-26 days). The total length of hospital stay took on average 23.6 days (range 9-33 days). Skin excoriation and bullae due to irritation by the traction occurred in 21 children (91.3% cases). All the bullae healed, in 4 (17.4%) patients minor scars of 1x1 cm in size were formed around ankles. Not a single patient developed the compartment syndrome. The average femoral shortening after the removal of traction was 0.8 cm (range 0-2.3 cm). The follow-up examination, performed on average 47.8 months (range 22-85 months) from the date of injury revealed the average discrepancy of spinomalleolar distances in both the lower limps of 0 cm (range -1 to 1 cm). Radiographically measured lengths of both the femurs showed the average difference of 0 cm (range -1.4 to 0.9 cm). The resulting average overgrowth of injured femur was 0.9 cm (range 0.1 to 3.2 cm). Scoliosis of the spine was not reported in any of the patients. In 3 patients femur alignment demonstrated rotation, namely an external rotation of 10° in all the cases. All the children demonstrated full hip and knee joint mobility, identical to the uninjured side. After a heavy load one patient reported pain in the thigh and one walked with limp. The other patients showed no problems whatsoever. Treatment with the use of Bryant's traction was well tolerated by parents. Altogether 15 parents (65.2%) would opt for the same treatment method in case of a recurrent injury. The home traction option would be welcomed by 17 parents (73.9%). DISCUSSION The treatment by Bryant's vertical traction is condemned in Anglo-Saxon countries due to the risk for developing compartment syndrome, described in earlier studies. Neither our cohort, nor more recent studies reported the occurrence of compartment syndrome. The most frequent complication faced in our study was the skin complications underneath the traction, namely in a total of 91.3% of patients. In the literature, the other authors only make references to bullae occurrence, but do not provide any further specifications. Overgrowth after femoral shaft fractures is a very well described phenomenon. The size of femoral overgrowth described in our study was similar to that referred to in the available literature. A method frequently used abroad is the so-called home traction. This method, however, has so far failed to take root in our country, even though this therapeutic technique would be appreciated by parents. CONCLUSIONS The treatment of femoral shaft fractures by Bryant's vertical traction, in children up to the weight of 15 kg, is a simple and safe method with excellent functional outcomes and minimum serious complications. When treating the children with the body weight more than 15 kg, the risk of bullae formation increases, therefore in this weight category treatment shall be decided upon on a case by case basis. The resulting average overgrowth of injured femur was 0.9 cm which corresponds with the findings of other authors. The treatment method using the Bryant's traction is well tolerated by parents, even though most of them would welcome the option of home traction. Key words: traction, femur fracture, overgrowth, children.
Keywords: trakce; Infant; Length of Stay; předškolní dítě; Humans; Traction; mužské pohlaví; Child, Preschool; Femoral Fractures; fraktury femuru; Infant, Newborn; výsledek terapie; Accidents, Traffic; délka pobytu; Treatment Outcome; novorozenec; ženské pohlaví; lidé; dítě; Child; dopravní nehody; Male; kojenec; Female